La Razón Irónica en las Tradiciones Peruanas - Arista Montoya, Luis Alberto (2018)
Yes. It is possible to carry out a philosophical reading of the Peruvian Traditionsof Ricardo Palma (7th February 1833- 6th October 1918). Therefore, throughouthis narrative it runs the metaphysics of the customs of his time using the aestheticalmethod of the sociological irony, linking it with the critique of cynical reasondeveloped by some philosophers.